Enantioselective Assembly of Fully Substituted α‐Amino Allenoates Through a Mannich Addition and Stepwise [3,3]‐σ Rearrangement Sequence - Haoxuan Yuan; Yi Zhou; Xiongda Xie; Ming Bao; Kewei Chen; Kemiao Hong; Zhixiang Yu; Xinfang Xu (Advanced Science)
Abstract Chiral fully‐substituted allenes are synthetically significant and pivotal building blocks that can engage in diverse transformations toward a variety of bioactive molecules. The enantioselective assembly of these skeletons using readily available reactants offers significant advantages but remains challenging. Herein, an asymmetric formal Michael‐type addition of alkynyl imines with the key alkylgold intermediates derived in situ from N‐propargylamides is accomplished under gold‐complex and chiral quinine‐derived squaramide (QN‐SQA) synergetic catalysis. Control experiments and the density functional theory (DFT) calculations indicated that this cascade reaction involves a Mannich‐type addition and stepwise [3,3]‐σ rearrangement sequence, leading to the fully substituted α‐amino allenoates, which are elusive and take multi‐step to prepare with other methods, in high yields and excellent enantioselectivity.